PENGARUH HASIL BELAJAR MATA PELAJARAN KEWIRAUSAHAAN DAN LINGKUNGAN KELUARGA TERHADAP MINAT BERWIRAUSAHA DENGAN SELF EFFICACY SEBAGAI VARIABEL INTERVENING - Faddel Muhammad; Rose Rahmidani (Jurnal Pendidikan Ekonomi (JURKAMI), 2025)
This research aims to analyse the effect of entrepreneurship learning outcomes and family environment on entrepreneurial interest with self-efficacy as an intervening variable. This study is associative in nature. The population in this study were students in grades XI and XII at SMKN 6 Padang. The sample size was determined to be 100 samples using the Slovin formula and proportional random sampling technique. The data used is primary data obtained through the distribution of questionnaires to students in grades XI and XII at SMKN 6 Padang. The data analysis techniques used are descriptive analysis, classical assumption testing, path analysis, t-test and Sobel test using SPSS software. The results of the study showed that: 1) Learning outcomes did not have a significant effect on entrepreneurial interest, 2) Family environment had a significant effect on entrepreneurial interest, 3) Self-efficacy has a significant effect on entrepreneurial interest, 4) Academic achievement does not have a significant effect on self-efficacy, 5) Family environment has a significant effect on self-efficacy, 6) Academic achievement does not have a significant effect on entrepreneurial interest through self-efficacy, 7) Family environment has a significant effect on entrepreneurial interest through self-efficacy. The limitations of this study are the limited research time and sample size, as well as the addition of other variables that influence entrepreneurial interest.